THE ESSENCE OF THE DIGITAL ECONOMY AND KEY FEATURES OF THE DEVELOPMENT OF COMMUNICATION SERVICES - Nazarov Sanjar Nasridinovich (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2024)
The digital economy represents a transformative phase in global economic development, driven by technological advancements, data proliferation, and interconnectedness. At its core, the digital economy encompasses economic activities enabled by digital technologies, fostering innovation, efficiency, and new business models. It leverages the power of big data, artificial intelligence, cloud computing, and the Internet of Things (IoT) to redefine value creation, distribution, and consumption. The development of communication services plays a pivotal role in this evolution, as they form the backbone of the digital economy. Key features include the rapid expansion of high-speed internet, mobile connectivity, and the integration of advanced technologies like 5G, which enhance real-time communication and data transfer capabilities. Additionally, communication services have increasingly shifted toward platforms and ecosystems, emphasizing user engagement, personalization, and seamless interoperability.